Standardization of screen sizes and density grades for chilli (Capsicum annuum) seed processing - K. VISHWANATH; H.M. PALLAVI; U.S. CHANDRASHEKAR (Seed Research, 2026)
Seeds of chilli (Capsicum annuum L.) cv Byadagi were size graded by using different screen sizes, viz. 2.50mm(R) (S_{1}) 2.80mm(R) (S_{2}) 3.10mm(R) (S_{3}) 3.25mm(R) (S_{4}) and density grades D_{1}(1gcc - 1) to D_{4} (1.06 gcc-1), and evaluated for seed quality parameters. The results showed that seed size grades were found to influence seed recovery, test weight, germination and other seed quality parameters such as root length, shoot length, seedling dry weight, vigour index, field emergence, speed of emergence and germination after accelerated ageing. Though S_{4} (3.25mm(R)) seeds showed higher seed quality parameters, they recorded poor seed recovery (68%). Seed size 2.50mm(R) (S_{1}) could be employed with least reduction in seed quality and with high recovery (92%). In seed density grades, despite improvement in D_{3} (1.04 gcc-1) and D_{4} (1.06 gcc-1) density grades, seed recovery was as low as 75 and 66%, respectively. Thus, D_{2} (1.02gcc-1) density grade seed which accounted for seed recovery of 83% was identified as ideal for upgrading seeds.